Analisis Keputusan Pembelian Smartphone pada Gen-Z - Rizqon Jamil Farhas (Journal of Engineering Science and Technology Management (JES-TM), 2021)
The purpose of this study was to determine consumer decisions in purchasing Smartphones for people who visited the Pekanbaru Mall shopping center. The sample is determined proportionally as many as 50 people with a purposive non-probability sampling technique, namely consumers of generation z who use smartphones. The data collection technique used a questionnaire and the data were analyzed by quantitative descriptive analysis of percentages. Based on the results of the study it can be concluded that; 1) The dimension of brand choice has the highest average of 4.19, meaning that consumers prioritize the search for the most suitable brand including brand interest, brand habits and price conformity with the brand being the most prioritized in the purchasing decision process. 2) The dimension of product choice has the lowest average, which is 3.59, meaning that consumers consider a smartphone to have become an ordinary need and it is natural for everyone to have it because it is a need for a wider means of communication than the use of ordinary GSM mobile phones including needs, values, lifestyle stimulus and level of dependence